2013
DOI: 10.1371/journal.pone.0055719
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-9 Suppresses the Proliferation, Invasion and Metastasis of Gastric Cancer Cells through Targeting Cyclin D1 and Ets1

Abstract: Recent evidence shows that altered microRNA-9 (miR-9) expression is implicated in the progression of gastric cancer. However, the exact roles and underlying mechanisms of miR-9 in the proliferation, invasion and metastasis of gastric cancer still remain unknown. In this study, miR-9 was found to be down-regulated and inversely correlated with the expression of cyclin D1 and v-ets erythroblastosis virus E26 oncogene homolog 1 (Ets1) in gastric cancer tissues and cell lines. Bioinformatics analysis revealed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
118
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(126 citation statements)
references
References 50 publications
7
118
0
1
Order By: Relevance
“…Recent studies have demonstrated that cyclinD1 has been associated with tumor invasion and metastasis in clinical studies and in vivo experiments, and cyclin D1 regulates invasion and metastasis through the phosphorylation of paxillin. [24][25][26] In addition to the suppression of cell growth by SOX6 in the ovarian cancer cells, inhibitory effect of SOX6 on ovarian cancer cell invasion was also observed in this study, suggesting that SOX6 may prevent metastasis of ovarian tumors. The SOX family of transcription factors has emerged as modulators of canonical Wnt/β-catenin signaling in diverse development and disease contexts.…”
Section: Discussionsupporting
confidence: 67%
“…Recent studies have demonstrated that cyclinD1 has been associated with tumor invasion and metastasis in clinical studies and in vivo experiments, and cyclin D1 regulates invasion and metastasis through the phosphorylation of paxillin. [24][25][26] In addition to the suppression of cell growth by SOX6 in the ovarian cancer cells, inhibitory effect of SOX6 on ovarian cancer cell invasion was also observed in this study, suggesting that SOX6 may prevent metastasis of ovarian tumors. The SOX family of transcription factors has emerged as modulators of canonical Wnt/β-catenin signaling in diverse development and disease contexts.…”
Section: Discussionsupporting
confidence: 67%
“…miR-9 has also been shown to target CDH-1 mRNA, which downregulated the expression of E-cadherin, thereby increasing the nuclear translocation of β-catenin and enhancing its binding with transcription factors TCF/LEF, in order to upregulate the transcription of genes that facilitate cell proliferation and angiogenesis . Zheng et al (2013) identified cyclin D1 and Ets1 as new targets of miR-9 in gastric cancer; moreover, they demonstrated that miR-9 suppressed the proliferation, invasion, and metastasis of gastric cancer cells. In this study, miR-9 was found to play an oncogenic role in osteosarcoma; however, the precise mechanism with which miR-9 influences osteosarcoma tumorigenesis and progression remains to be understood.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, among the miRNAs that significantly inhibited Salmonella infection by at least 1.5-fold in the screening we found several miRNAs that have been reported to inhibit G1/S transition, namely miR-7, miR-9, miR-26a and miR-26b [28][29][30] . We validated the effect of these miRNAs on Salmonella infection (Fig.…”
Section: Screening For Mirnas Controlling Salmonella Infectionmentioning
confidence: 92%